Igor Severyanin’s poetry in translation into Polish. Tradition and innovation (two examples) - Bednarczyk, Anna (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2018)
The article considers the translation of two poems by Igor Severyanin into Polish. In the first case a translational analysis of the source and the target text is offered. The second case is an example of a pre-translation analysis followed by an attempt to make a translation. What is taken into account is the issue of the old combining with the new, the innovative with the traditional in the works of the poet (on the level of vocabulary, imagery and form) and the task of reproducing this fusion in translation. The analysis indicates examples of the translator’s compensations for certain lost elements of the source texts.